Mechanism and Challenges of Legislative Carry Over in Indonesia’s: Institutional Design and Normative Formation Issues - Kusuma Putra, Rengga; Milthree Saragih, Geofani; Hermanto, Bagus; Khasanah, Dian Ratu Ayu Uswatun; Yusof, Fablli (Universitas Islam Negeri Walisongo Semarang, 2025)
This study explores the legislative Carry Over mechanism within the Indonesian legal framework, with particular attention to its institutional design, implementation challenges, and procedural dimensions. Employing a normative juridical method complemented by a comparative legal approach, the research analyzes how the Carry Over mechanism functions in practice and its implications for legislative continuity across parliamentary terms. The findings suggest that while the Carry Over concept offers a pathway for sustaining legislative deliberation beyond a single legislative period, its application in Indonesia remains hindered by a number of structural and technical obstacles. These include persistent legal uncertainty, shifts in political direction following changes in parliamentary composition, and questions regarding the democratic legitimacy of continuing draft laws without renewed public or legislative scrutiny. In response to these concerns, the study proposes a set of policy reforms, including the establishment of clearer regulatory frameworks, enhanced procedural accountability, and stronger inter-institutional coordination—each aimed at reinforcing the effectiveness and legitimacy of the Carry Over mechanism within Indonesia’s legislative process. Studi ini mengkaji mekanisme Carry Over dalam kerangka hukum Indonesia, dengan fokus khusus pada desain institusionalnya, tantangan implementasi, dan dimensi proseduralnya. Menggunakan metode yuridis normatif yang dilengkapi dengan pendekatan hukum komparatif, penelitian ini menganalisis bagaimana mekanisme Carry Over berfungsi dalam praktik dan implikasinya terhadap kelanjutan legislatif antar periode parlemen. Temuan menunjukkan bahwa meskipun konsep Carry Over menawarkan jalur untuk mempertahankan pembahasan legislatif melampaui satu periode legislatif, implementasinya di Indonesia masih terhambat oleh sejumlah hambatan struktural dan teknis. Hambatan tersebut meliputi ketidakpastian hukum yang persisten, pergeseran arah politik setelah perubahan komposisi parlemen, dan pertanyaan mengenai legitimasi demokratis melanjutkan rancangan undang-undang tanpa pengawasan publik atau legislatif yang diperbarui. Sebagai tanggapan atas kekhawatiran ini, studi ini mengusulkan serangkaian reformasi kebijakan, termasuk pembentukan kerangka regulasi yang lebih jelas, peningkatan akuntabilitas prosedural, dan koordinasi antar lembaga yang lebih kuat—masing-masing bertujuan untuk memperkuat efektivitas dan legitimasi mekanisme Carry Over dalam proses legislatif Indonesia. Keywords: Carry Over; Legislation; Indonesian laws and regulations.